Importance of technologies characteristics for VPPs - Morais, H. (2013)
The large increase of renewable energy sources and Distributed Generation (DG) of electricity gives place to the Virtual Power Producer (VPP) concept. VPPs can reinforce the importance of these generation technologies making them valuable in electricity markets. One of the most important tasks of a VPP is the conjugation of technologies to obtain a consistent set of associated producers and allow them to operate in the electric market. This paper presents some characteristics regarding already existent technologies and relevant aspects for producers and for VPP.